Técnicas de mitigação de interferência eletromagnética em equipamentos de iluminação a LED - Pedroni, Rafael (2017)
This dissertation introduces techniques for mitigation of conducted electromagnetic interference in lighting equipment using LEDs. This dissertation intends to offer the theoretical basis necessary for the development of the EMI filters project. Theoretical aspects are initially presented, in order to elucidate technical concepts regarding conducted electromagnetic interference. The proposed techniques for mitigation of electromagnetic interference can be classified in: layout of the printed circuit board, suitable choice and positioning of electronic components and design of filters. This dissertation addresses the issue through a study of a buck-boost converter used as driver in a tubular LED lamp. The current spectrum was obtained and, based on this result, a π filter was designed for noise attenuation. A printed circuit board was developed according the rules for decreasing the interferences. For the filter project, three different inductors were analysed, being the coupled inductor in series with a differential mode inductor the best compromise between performance and volume.